1984
DOI: 10.1152/jappl.1984.56.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to a high-fat diet that increase exercise endurance in male rats

Abstract: Eighty-seven male Sprague-Dawley rats (245-300 g) were randomly assigned to one of two experimental groups. The first group consumed a diet high in fat and low in carbohydrate (LCD), whereas the second group ate a normal diet (ND). After either 1 or 5 wk on the diets, rats from each group were killed either before or after an exhausting run on a rodent treadmill (35 m X min-1, 0% grade). The LCD animals ran significantly longer before exhaustion at both week 1 (44.9 +/- 5.1 vs. 41.6 +/- 4.2 min) and week 5 (47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
98
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 0 publications
9
98
2
Order By: Relevance
“…Both exercise training and high-fat diet consumption induce an increase in mitochondrial biogenesis in skeletal muscle (1,(5)(6)(7). Increased muscle mitochondria induced by endurance exercise training were previously thought to develop through a slow process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both exercise training and high-fat diet consumption induce an increase in mitochondrial biogenesis in skeletal muscle (1,(5)(6)(7). Increased muscle mitochondria induced by endurance exercise training were previously thought to develop through a slow process.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al (5) reported that feeding a high-fat diet for only 1 wk increased muscle 3-hydroxyacyl CoA dehydrogenase activity and endurance exercise capacity, without effects on other mitochondrial enzymes, such as citrate synthase. These results suggest that fatty acid b-oxidation is responsible for the high-fat diet-induced increase in endurance capacity.…”
Section: Discussionmentioning
confidence: 99%
“…A high-fat diet and elevated levels of plasma fatty acids lead to increases in the activity of citrate synthase, 3-hydroxyacyl-CoA dehydrogenase and carnitine palmitoyl-transferase 17,29,35,38 and induce increased biogenesis of mitochondria in skeletal muscle, 39,40 all of which would act to potentially increase fatty-acid metabolism. These effects can appear in only a matter of days, and in some cases reach their maximum levels within a week.…”
Section: Discussionmentioning
confidence: 99%
“…These effects can appear in only a matter of days, and in some cases reach their maximum levels within a week. 17,19 However, high-fat diets can also lead to higher levels of mitochondrial uncoupling protein (UCP3), which reduces the efficiency of energy production and, therefore, can impair exercise capacity. 41 Although the precise limitation(s) on endurance exercise performance depend on the intensity and/or duration of the activity, the depletion of energy substrates is a commonly considered cause of fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation